The Influence of Lifestyle and Consumer Attitudes on Purchase Decisions through Customer Satisfaction at Cafe Brogul Makassar - Rr Dyah Eko Setyowati (Universitas Dharma Wacana, 2022)
This study aimed to analyze the lifestyle and consumer attitudes towards purchasing decisions through customer satisfaction at the Brogul cafÃ© in the city of Makassar. This research is quantitative. The selection of research sites was carried out by purposive sampling, namely, choosing research locations intentionally by considering specific aspects, namely Cafe Brogul Makasar as a fostered MSME of the Indonesian Women's Empowerment Forum (FPPI). The data analysis method used in this study used quantitative descriptive analysis methods. This study's data instrument testing consisted of validity and reliability. The data analysis technique in this study consisted of Normality Test, Model Suitability Test, and Hypothesis Testing. Based on the analysis and discussion above, it can be concluded that, among others, Lifestyle and Consumer Attitudes have an influence on Customer Satisfaction, Lifestyle and Consumer Attitudes have a positive and significant impact on Purchase Decisions, the greater the effect of customer satisfaction, the greater the purchase decision